Sublingual allergen-specific immunotherapy adjuvanted with monophosphoryl lipid A: a phase I/IIa study - Pfaar, Oliver; Barth, Christine; Jaschke, Christine; Hörmann, Karl; Klimek, Ludger (International archives of allergy and immunology, 2011)
BACKGROUND: Sublingual immunotherapy (SLIT) allergy vaccines have an excellent safety profile, but opinions vary on their efficacy, and treatment regimens are often lengthy. This study assessed the effects of the Toll-like receptor 4 agonist monophosphoryl lipid A (MPL®) on safety/tolerability and clinical and immunological efficacy when combined with grass pollen SLIT formulations in treating patients with seasonal allergic rhinitis. This is the first reported study of adjuvanted SLIT. - METHODS: In this double-blind placebo-controlled phase I/IIa study, 80 grass pollen-sensitive subjects were randomized into 4 groups of 20 subjects to receive daily treatment for 8 weeks. Sixteen patients per group received SLIT and 4 received placebo. The formulation given to each group varied with respect to grass pollen extract and MPL content. Grass allergen nasal challenge tests (NCTs) were performed prior to dosing and in weeks 4 and 10. Grass pollen-specific immunoglobulin G (IgG) and IgE antibodies were measured at baseline and prior to dosing in weeks 2, 3, 4, 5 and 10. - RESULTS: Local and systemic adverse events were generally comparable for patients who received active treatment and placebo. Patients in the 2 groups given SLIT containing the highest amount of MPL experienced the highest proportion of negative NCTs after 10 weeks (47 and 44%, vs. 20% with placebo). These patients also showed earlier median increases in specific IgG and smaller increases in IgE levels than those receiving other formulations. - CONCLUSIONS: These results suggest that SLIT preparations containing MPL are well tolerated and alter the immunological response to grass antigens after 3 weeks of exposure, with an associated suppression of nasal challenge responses.